Epidemiology of brain tumours in Kyrgyz Republic: a population based study - K. B. Yrysov; M. B. Yrysova (Бюллетень сибирской медицины)
Brain tumours cause considerable concern due to a high mortality and there are increasing efforts to provide adequate care. The goal of this study was to determine the incidence of brain tumours in Kyrgyz Republic. A population based study was performed. Patients from Kyrgyz Republic with incident intracranial tumours diagnosed in 2005 and 2007 (by CT, MRI or histology) were identified retrospectively using multiple sources. Differences in incidence by tumour type, age and sex were examined. Eight hundred and eighty four patients with incident brain tumours were identified (456 primary tumours and 428 secondary tumours). The commonest primary tumours were neuroepithelial tumours (53,5%), meningeal tumours (19,5%), and sellar tumours (16,5%). The crude yearly incidences of primary and secondary tumours were 30,3 and 28,3 per 100 000 respectively. About 50% of patients with secondary tumours had an underlying lung cancer. The incidence of primary and secondary tumours increased markedly with age. Meningeal tumours were more common in women. This study shows that the incidence of intracranial tumours in Kyrgyz Republic is considerably higher than previously thought. Brain tumours are a significant cause of morbidity and mortality in Kyrgyz Republic, and further research into their aetiology and treatment is urgently required.